Induksi Sintesa Kurkuminoid Dalam Kalus Temulawak (Curcuma Xanthorriza, Roxb) Akibat Pengaruh Hormon 2,4-D Dan Fenilalanin Pada Media Kultur - Yudi Rinanto (Jurnal Farmasi Indonesia, 2009)
The addition of precursor into in vitro Murashige Skoog (MS) media culture expected to be able improve curcuminoid synthesis within the callus. Phenylalanine is precursor in curcuminoid synthesis. 2,4-D hormone is also added into media culture to induce callus formation. The concentration of 2,4-D hormone and phenylalanine is 0, 2 and 4 ppm, respectively. The qualitative analysis was done with color reaction and Thin Layer Chromatography (TLC) with gel silicon GF254 as stationary phase and chloroform : ethanol 96%: glacial acetic acid (94:5:1) as movement phase and detected by the visible ligh. The quantitative analysis was done by measuring the spot area in the TLC chromatogram with TLC scanner, and then was calculated using standart curcumin curve. Base on the experiment indicates 2,4-D Hormone with 4 ppm result the fastest time callus induction. Curcuminoid content is higher in rhizome compared in callus. The combination of 2,4-D hormone and phenylalanine yield the higher curcumin content than desmetoxi-curcumin for each treatment combination. The highest curcumin content is produced by 2,4-D hormone and phenylalanine combination with 4 ppm concentration that is 0,39 %. Meanwhile the highest desmetoxi-curcumin is produced by 2,4-D hormone and phenylalanine combination with 4 and 2 ppm concentration, respectively, that is 0,18 %. 2,4-D hormone and phenylalanine affects more significantly in curcumin synthesis rather than desmetoxi-curcumin.